The financial sector in the Kingdom of Saudi Arabia’s Vision 2030: Evaluation and achievements - Matyori, Emad Adnan (Journal of Economic, Administrative and Legal Sciences, 2025)
The study aimed to monitor the reality of implementing the financial sector development program in the Kingdom of Saudi Arabia in accordance with Vision 2030 AD. By reviewing the financial sector development program document in accordance with Vision 2030 AD, including the assessment of the financial sector and its expected role in supporting the development of the economy of the Kingdom of Saudi Arabia, specified in six goals, and comparing the target and the achieved or what has been accomplished - so far - through the statistics of the relevant indicators; The study concluded in general that the performance of the financial sector in supporting the economy is positive and exemplary and is moving quickly towards achieving the goals set for it by 2030 AD. Accordingly, the study recommended reviewing the targets set in the financial sector development programs and constantly updating them according to the actual performance in order to take advantage of the possible opportunities as a result of the sector’s accelerated positive performance. Also conducting studies to monitor the performance of other sectors targeted at strengthening the national economy, especially services such as health, education, and others, and comparing their performance with what is planned in Vision 2030; To reveal the level of achievement achieved; To support and rationalize corrective decision-making and enhance strengths; The simultaneous growth of different sectors enhances the concept of development and goes beyond economic growth, which has a limited impact compared to development.